10-6x-3=1

Simple and best practice solution for 10-6x-3=1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 10-6x-3=1 equation:


Simplifying
10 + -6x + -3 = 1

Reorder the terms:
10 + -3 + -6x = 1

Combine like terms: 10 + -3 = 7
7 + -6x = 1

Solving
7 + -6x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7' to each side of the equation.
7 + -7 + -6x = 1 + -7

Combine like terms: 7 + -7 = 0
0 + -6x = 1 + -7
-6x = 1 + -7

Combine like terms: 1 + -7 = -6
-6x = -6

Divide each side by '-6'.
x = 1

Simplifying
x = 1

See similar equations:

| 24(x+3)=0 | | 28-z=5 | | 2+14a=20a-5a | | z*z-(2+1i)z+(-1+7i)=0 | | -5x+2(-5x-5)=125 | | 2a+14a=20a-5a | | k/9=/18 | | 3-21=3x-9-2x | | -x+70=-86+5x | | 4(3x+2)-18= | | 6(z+2)-(6+4z)=z | | 3(x-3)=4(x+2) | | (4+4)(x+2)=(2+2) | | -5x=2x | | x^2-12x=8064 | | 8(5k-3)=-264 | | x^2-12x=5440 | | 9(y+5)=8y-6 | | 125*.38= | | -2x+2(-4x-3)=74 | | 4(y-8)=9+5y | | 28-6(2x+4)= | | 3(x+2)=4(x+2) | | 2x-1=63 | | z-(2+1i)z+(-1+7i)=0 | | 3(d-0.8)=4x+4 | | -34+3x=18+5x | | 19.3-4.507= | | 5x-31=2x+8 | | x+73=3x+9 | | 1-a^2=x^2-2ax+1 | | -6(2t+6)=-12 |

Equations solver categories